Employee Performance Reviewed from Discipline and Mutation with Job Satisfaction Mediation at The Surakarta Religious Court Class Ia - Sri Muhammad Kusumantoko; Istiatin Istiatin; Ida Aryati DPW (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study specifically aims to examine and analyze the influence of work discipline and transfer implementation on employee job satisfaction at the Surakarta Class IA Religious Court. Furthermore, this study is designed to evaluate the direct impact of work discipline, transfer, and job satisfaction on employee performance, and to analyze the extent to which job satisfaction can act as a mediating variable in the relationship. The methodology applied in this study is a quantitative descriptive approach. The research location is at the Surakarta Class IA Religious Court Office, involving a population of 40 employees. The sampling technique used is the census method (total sampling), so that all members of the population are used as research respondents. The primary data collection process was carried out using questionnaires, observations, and documentation, which were then processed and analyzed using the path analysis method. The data analysis technique applied is a variance-based Structural Equation Modeling (SEM) using the Partial Least Square (PLS) method through SmartPLS software. The results of the data analysis indicate that work discipline and transfer have a positive and significant effect on employee job satisfaction and performance. Job satisfaction was also found to have a positive and significant direct effect in improving employee performance. Finally, the mediation hypothesis test confirmed that job satisfaction functions significantly as a partial mediation variable, both in bridging the influence of work discipline on performance and the influence of transfers on employee performance achievements at the Surakarta Class IA Religious Court.